Deteksi dini kondisi kesehatan jiwa Kader kesehatan jiwa di PIK-R Kirana Kota Jambi - Nasution, Riska Amalya; Meinarisa, Meinarisa; Kamariyah, Kamariyah; Falani, Ilham; Yaldi, Destri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
Early detection of mental health is one of the crucial steps in maintaining a good quality of life. By recognizing the early symptoms of mental disorders, individuals can get the right intervention immediately, thus preventing the condition from developing into a more serious one. This not only helps in faster recovery, but also reduces the negative impact on social, occupational and educational aspects. Therefore, awareness of the importance of early detection should continue to be raised in the community, so that more people can lead healthier and happier lives. This community service aims to detect the mental health of cadres at PIK-R Kirana Jambi City. Data collection was carried out using the Mental Health Continuum-Shortform / MHC-SF questionnaire instrument. Data analysis of this detection was carried out using descriptive qualitative methods. The participants in this activity amounted to 19 cadres consisting of 9 men and 10 women, with an average age of 22.4 years. Based on the results of the detection and analysis that has been carried out on the data, information obtained as many as 1 person (5%) is in the Languishing category, 3 people (16%) are in the Moderate category, and 15 people (79%) are in the Flourishing category.